1983
DOI: 10.1111/j.1365-2621.1983.tb10765.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Velocity Effect on Heat Penetration Parameters During Institutional Size Retort Pouch Processing

Abstract: Institutional size retort pouches (15 X 12 X 1") filed with 10% bentonite were processed in water with overriding air pressure. The heat penetration parameter, fh, was measured at seven flow rates from 10 gal/min (Re = 3000) to 110 gal/min (Re = 33000). Apparent convection heat transfer coefficients (h-values) were calculated. Significant differences were found for both the h-value and observed fh value as a function of flow rate. The h-values ranged from 33-48 BTU/hr ft2 F and the observed fh values ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…Large unknown variations in the h values could actually cause a potential health hazard (5). The heat transfer coefficient between a can and steam is considered near infinite, but this is not the case for pouches in either pressurized water or steam-air mixture (5). Peterson and Adams (5) and Adams et al (6) used the equation developed by Ball and Olson (7) based on the slope index of the heating curve applied to infinite slab geometry to determine apparent heat transfer coefficients under varied retort heating medium and recirculation rate regimens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large unknown variations in the h values could actually cause a potential health hazard (5). The heat transfer coefficient between a can and steam is considered near infinite, but this is not the case for pouches in either pressurized water or steam-air mixture (5). Peterson and Adams (5) and Adams et al (6) used the equation developed by Ball and Olson (7) based on the slope index of the heating curve applied to infinite slab geometry to determine apparent heat transfer coefficients under varied retort heating medium and recirculation rate regimens.…”
Section: Introductionmentioning
confidence: 99%
“…This is also the case with the pasteurization of sous vide foods. Large unknown variations in the h values could actually cause a potential health hazard (5). The heat transfer coefficient between a can and steam is considered near infinite, but this is not the case for pouches in either pressurized water or steam-air mixture (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pflug and Barrerro (1967) observed that heat transfer coefficient was one of the critical processing factors. The rate of heat transfer depends on the circulating rate of the heating medium across the pouch surface (Peterson and Adams 1983). Rotation or agitation will help in faster heat penetration and quicker attainment of the recommended Fo value.…”
Section: Introductionmentioning
confidence: 99%
“…Two heat transfer coefficients were determined, the first being between the pressurized-water heating medium and the aluminum cassette, which was determined by an aluminum test brick method, and the second being that between the cassette and the pouch. Peterson and Adams (1983) and Adams et al (1983) used equations based on the slope index of the heating curve applied to infinite slab geometry to determine apparent heat transfer coefficients under varied retort heating medium and recirculation rate regimens. The term apparent is used to describe the value because in addition to the external heat transfer coefficient between the media and the pouch, the resistance to heat transfer of the rack and pouch material is also included.…”
Section: Introductionmentioning
confidence: 99%